Convection Theory and Relevant Problems in Stellar Structure, Evolution, and Pulsational Stability I Convection Theory and Structure of Convection Zone and Stellar Evolution - Xiong, Da-run (Frontiers in Astronomy and Space Sciences, 2021)
A non-local and time-dependent theory of convection is described briefly. This theory was used to calculated the structure of solar convection zones, evolution of massive stars, and lithium depletion in the atmosphere of the Sun and of late main sequence stars. The results show that: 1) The theoretical turbulent velocity and temperature fields and the convective envelope structure of the Sun agree with the observations and inferences from helioseismology inversion very well. 2) The theoretical evolution tracks for massive stars are at higher luminosity in comparison with those calculated using local mixing-length theory. This means that the evolution masses for a given luminosity were overestimated by the local MLT, which may be part of the reason for the contradiction between the evolution and pulsation mass of Cepheid variables. In comparison with the local MLT, our theoretical main sequence band becomes noticeably wider, which alleviates the contradiction between theoretical and observed distributions of luminous stars in the H-R diagram. The semi-convection contradiction was removed automatically, as predicted by us. 3) The predicted lithium depletion, in general, agrees well with the observation of the Sun and Galactic open clusters of different ages.